The diurnal and seasonal variations of the Surface Wind at Visakhapatnam - Agarwala, K.S. (MAUSAM, 1953)
The present paper discusses the diurnal and seasonal variations of the wind at" Visakhapatnam at a height of 56½ ft above ground based on three years' data 1939-41. Curves showing the mean diurnal variation of the wind speed for the twelve months of the year are given and discussed; these curves show a strong maximum in the early afternoon. A rough estimate of the value of the co-efficient of eddy diffusion works out to be 137 in C;G.S. units. Tables of frequencies of prevailing wind direction at 3-hourlyinterva1sfor each month or the year are given and their main features are described; a table showing the diurnal variation of' calms also included. The general characteristics of land and sea breezes occurring at the station are briefly mentioned The annual variation of the speed and direction of wind as well as its steadiness is also briefly discussed. The mean monthly steadiness is found to vary from 60 to 92 per cent.